In-situ hydrogen generation from 1, 2, 3, 4-tetrahydronaphthalene for catalytic conversion of oleic acid to diesel fuel hydrocarbons: Parametric studies using Response Surface Methodology approach. (2nd August 2019) - Cheah, Kin Wai; Yusup, Suzana; Kyriakou, Georgios; Ameen, Mariam; Taylor, Martin J.; Nowakowski, Daniel J.; Bridgwater, Anthony V.; Uemura, Yoshimitsu
Abstract: This work reported a new strategy in producing synthetic diesel hydrocarbons from a mono-unsaturated fatty acid model compound, oleic acid and replacing high pressure molecular hydrogen with a hydrogen-rich donor solvent, 1, 2, 3, 4–tetrahydronaphthalene for the first time. Under the absence of an external H2 supply, oleic acid was dispersed in 1, 2, 3, 4-tetrahydronaphthalene and hydrotreated over commercially available 5 wt% Pd/C in a fed-batch reactor to obtain diesel range fuel products. A maximum oleic acid conversion of 92.4% and highest diesel hydrocarbon selectivity of 67.4% were achieved at 330 °C with a solvent to fatty acid mass ratio of 1 for 3 h under autogenous pressure. In-situ H2 produced from 1, 2, 3, 4-tetrahydronaphthalene operated as an effective hydrogen donor vehicle that continuously transported active hydrogen species from gas phase to reactant acid molecules and radical fragments. It minimized polymerization of reaction intermediate and suppressed coke formation, which subsequently improved catalyst resistance toward deactivation. Graphical abstract: Image 1 Highlights: Decarboxylation of oleic acid to alkanes over Pd/C in 1, 2, 3, 4-tetrahydronaphthalene. Addition of 1, 2, 3, 4-tetrahydronaphthalene as donor solvent and H2 source. Tandem release of in situ H2 from 1, 2, 3, 4- tetrahydronaphthalene solvent. Up to 67.4 w.t% of diesel-like hydrocarbon selectivity was achieved after 3 h. Improve catalyst resistance toward deactivation and prolong catalyst lifetime.